2013
DOI: 10.1108/00251741311301858
|View full text |Cite
|
Sign up to set email alerts
|

Environmental knowledge, unlearning, and performance in hospitality companies

Abstract: The Spanish hospitality industry is facing environmental challenges which require organisations and individuals to learn new skills and practices and create new environmental knowledge. Methodology / Approach This paper analyses the relationships between an unlearning context and environmental knowledge and tries to identify whether environmental knowledge impacts on business outcomes through an empirical study of 127 Spanish hospitality companies. Findings The results support the hypothesis that, in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 71 publications
1
12
0
3
Order By: Relevance
“…A possible explanation for the significance of such an effect may be related to the fact that before environmental knowledge can be created specific assumptions should be established and shared. Failing to do so will result in only a few individuals within the organisation having access to such relevant knowledge resources, which in turn may lead to the under-utilisation of relevant knowledge or the utilisation of knowledge which is not relevant, both of which cases are likely to lead to a degradation of environmental knowledge (Cegarra-Navarro et al, 2013). One interpretation of this relationship is that through the knowledge management processes, a company can allow individuals to adjust their mental models and the nature of their assumptions to highlight some of the environmental issues and concerns that may have a direct effect on the entire company, its operation and results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A possible explanation for the significance of such an effect may be related to the fact that before environmental knowledge can be created specific assumptions should be established and shared. Failing to do so will result in only a few individuals within the organisation having access to such relevant knowledge resources, which in turn may lead to the under-utilisation of relevant knowledge or the utilisation of knowledge which is not relevant, both of which cases are likely to lead to a degradation of environmental knowledge (Cegarra-Navarro et al, 2013). One interpretation of this relationship is that through the knowledge management processes, a company can allow individuals to adjust their mental models and the nature of their assumptions to highlight some of the environmental issues and concerns that may have a direct effect on the entire company, its operation and results.…”
Section: Discussionmentioning
confidence: 97%
“…environmental routines and procedures) will change over time (Imran, Khorshed, & Narelle, 2014), requiring the modification of some knowledge structures (Aggeri, 1999;Brockhoff et al, 1999). Prior research has also shown that the effect of environmental initiatives on business performance can vary substantially in a turbulent context (Cegarra-Navarro et al, 2013), such as the Spanish hospitality sector during the period we have examined. In these circumstances it becomes necessary for hospitality companies to update their existing knowledge of environmental issues (Fraj, Matute, & Igu acel, 2015).…”
Section: Connecting Environmental Knowledge To the Seci Model Over Timementioning
confidence: 94%
“…But changes lead to OU [76,77]. Continuous change requires modifications not only to work routines but also to social practices [84]. Organizational change entails getting employees to adopt new behaviors that benefit the company [85].…”
Section: Organizational Unlearning As a Moderator Of The Relationshipmentioning
confidence: 99%
“…In fact, one of the essential organizational strategies to implement change is effective communication (i.e., good knowledge management). Companies must heed environmental changes and implement effective knowledge management to adapt rapidly to the turbulent, dynamic environment [84].…”
Section: Organizational Unlearning As a Moderator Of The Relationshipmentioning
confidence: 99%
“…Une telle prise de conscience est rendue possible par le recours à des outils spécifiques, tels que des campagnes de communication ou des formations spécifiques (Marcati et al, 2008) . Par conséquent, la présence d'un fort contexte interne favorisant le changement d'attitude est essentielle pour les organisations ayant une culture environnementale (Cegarra-Navarro et al, 2013) . La mise en place d'un tel contexte permet de réorienter les valeurs, normes et comportements organisationnels en modifiant les structures cognitives (Nystrom & Starbuck, 1984), les modèles mentaux (Day & Nedungadi, 1994), la logique dominante (Bettis & Prahalad, 1995) et les hypothèses de base qui guident le comportement (Shaw & Perkins, 1991) .…”
Section: L'effet Facilitant De La Culture Environnementaleunclassified